The Neural Impact of Mindfulness-Based and Somatic Practices on Music Performance Anxiety - Boland, Angela (Université d'Ottawa | University of Ottawa, 2026)
Background. Music performance anxiety and musculoskeletal disorders can lead to devastating outcomes for musicians, such as career abandonment and substance use. This thesis uses functional Magnetic Resonance Imaging (fMRI) to investigate the neurobiological mechanisms through which mindfulness-based and somatic interventions may improve musicians’ health and well-being. Studies 1 and 2 Methods. Studies 1 and 2 investigated the neural effects of a two-week-long mindfulness-based vocal improvisation program called Environmental Vocal Exploration or EVE. EVE involved vocalizing in a group setting while engaging with the body, breath, and surroundings. We also investigated the neural effects of a two-week-long traditional mindfulness program as an active control condition. Participants (N = 27) were 18–28-year-old musicians (n=10: traditional mindfulness, n=7: EVE, n=10: no intervention). Study 1 investigated pre-to-post-intervention changes in brain activity during an anxiety-provoking task and a working memory task, and Study 2 examined resting state fMRI results. Changes in state anxiety and themes from EVE discussion transcripts were also analyzed. Studies 1 and 2 Results. Following both interventions, particularly EVE, participants’ brain activity reflected increased emotional and attentional regulation. This aligned with reduced state anxiety and themes of present moment awareness that emerged. EVE’s benefits may surpass those of traditional mindfulness because vocalization stimulates the vagus nerve, which helps to reduce stress. Study 3 Methods. Among another group of 23 professional musicians, Study 3 investigated the neural effects of a somatic intervention called Body Mapping for Musicians (BMM), which took place over two formal sessions (eight hours total) and three weeks of self-guided practice. Body Mapping helps musicians correct and refine the internal representation of their body movement while playing an instrument or singing; techniques include retraining movements based on the body’s anatomy and retraining attention toward both internal and external sensations. Using fMRI, we examined pre- to post-intervention changes in brain activity during the aforementioned anxiety-provoking and working memory tasks. We also examined the effects of Body Mapping on subjective anxiety, mindfulness, musculoskeletal discomfort, and working memory performance. Themes from participants’ experiences with Body Mapping were also assessed. Study 3 Results. Following the intervention, participants’ brain activity reflected reduced emotional arousal during the anxiety-provoking task as well as enhanced sensorimotor integration during the working memory task. Additionally, state, trait, and performance anxiety decreased post-intervention. Themes of freedom in movement, breath, and awareness also emerged. Body Mapping for Musicians may thus reduce performance anxiety through enhanced sensorimotor processing and nonjudgmental awareness. Conclusion. These studies provide preliminary empirical findings on how mindfulness and somatic interventions may improve musicians’ health and well-being. Future studies may seek to build on this work, to further examine each intervention’s effects on a larger scale.
Keywords: Mindfulness; Music Performance Anxiety; Neuroimaging; Environmental Vocal Exploration; Body Mapping for Musicians